Identification and impact analysis of invasive species: A case study in the Mongla Sea Port Area of Bagerhat District of Bangladesh - Amin, Md Nurul; Ali, Mohd Yousuf; Salequzzaman, Md (Daffodil International University Journal of Science and Technology, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Manipulation through invasion is a major problem in most of the port areas in recent world. Mongla is an important sea port that has accomplished the activities like import and export of various goods inside and outside Bangladesh. The process not only involves the moving of goods, it also carries the invasive species purposely or accidentally which invading to the new location of the Mongla port area through exploration and colonization with varieties diversity and scale. The paper identifies the invasive species and analyses the causes and ways of invasion in the coastal waters with possible impacts of invasion in the Mongla Port area. To achieve the objectives of the research, different aquatic species were collected by random sampling from the confluence of the River Passur Mongla port and the adjacent area around the Sundarbans from September 2006 to April 2007. The fishermen and local communities including indigenous people were interviewed to explore the invasion situation. The research reveals that ballast water of cargo ships is one of the means of invasion of the coastal waters of Mongla Port. Aquaculture is another reason of invasion due to introduction of many exotic fishes and shrimp species such as Pangus (Pangasius sutchi), African Magur (Clarias gariepinus), Tilapia (Tilapia mossambica) and Nilotica (Oreochromis niloticus) etc. that have the active roles for altering the aquatic ecosystem of Mongla Port. Finally, the research also finds out some possible environmental impacts caused by those invasive species. Key words: Invasive species, Aquaculture, Indigenous species, Aquatic ecosystem, Ballast water DOI: 10.3329/diujst.v4i1.4353 Daffodil International University Journal of Science and Technology Vol.4(1) 2009 pp.35-41